Logic, Language, Information, and Computation 28th International Workshop, WoLLIC 2022, Iași, Romania, September 20-23, 2022, Proceedings - Ciabattoni, Agata; Pimentel, Elaine; de Queiroz, Ruy J. G. B. (Cham : Springer International Publishing : Imprint: Springer, 2022)
Edited in collaboration with FoLLI, the Association of Logic, Language and Information this book constitutes the refereed proceedings of the 28th Workshop on Logic, Language, Information and Computation, WoLLIC 2022, Iasi, Romania, in September 2022. The 25 full papers presented included with 8 extra abstracts, 5 invited talks and 3 tutorials were fully reviewed and selected from 46 submissions. The conference aims fostering interdisciplinary research in pure and applied logic.
Proof theory, -- Model theory -- Modal and temporal logics -- Automated reasoning.-Constraint and logic programming -- Constructive mathematics -- Equational logic and rewriting -- Finite Model Theory -- Descriptive complexity, -- Higher order logic -- Programming logic -- Model checking -- Type theory -- Lambda calculus -- Semantics of programming languages -- Computational linguistics.-Language and computation -- Logic and language.
Keywords: Logic; Artificial intelligence; Programming languages (Electronic computers).; Natural language processing (Computer science).; Computers; Compilers (Computer programs).; Logic; Artificial Intelligence; Programming Language; Natural Language Processing (NLP).; Computer Hardware; Compilers and Interpreters